Investigating Osteomyelitis as a Rare Adverse Effect of Vaccination in the Pediatric Population - Valeria Garbo; Laura Venuti; Chiara Albano; Costanza Caruana; Alessandra Cuccia; Anna Condemi; Giovanni Boncori; Valentina Frasca Polara; Antonio Cascio; Sergio Salerno; Claudia Colomba (Pathogens, 2024)
Immunization is a preventive measure of crucial importance. As with any other medication, side effects are a possibility and include the rare occurrence of severe infections, such as osteomyelitis. We report an unusual case of pediatric osteomyelitis following vaccination and provide a review of similar reports submitted to the Vaccine Adverse Event Report System (VAERS), aiming to explore the association between the vaccination procedure and the occurrence of osteomyelitis in childhood. A previously healthy infant, with no history of trauma or infection, presented with hyperpyrexia, swelling, and functional impairment in the left leg and was eventually diagnosed with osteomyelitis of the left femur. An edema was noted at the site of the injection that he received days before for immunization purposes. The infection required surgical drainage and a four-week-long intravenous antibiotic treatment, and the patient was discharged upon showing improved clinical conditions. Forty-seven reports of similar cases submitted to VAERS between 1994 and 2023 were collected, and several cases from the literature, including a case of femoral osteomyelitis in a newborn vaccinated against Hepatitis B, attributed to improper injection technique. Another case was reported in a 15-year-old girl, which aligned with six similar cases of osteomyelitis in adolescents following HPV vaccines collected from VAERS. Despite the small sample number, the findings that in 77% of cases the infection was localized in the vaccinated limb and that symptoms appeared on average 4.3 days (IQR 1.0–5.7 days) post-vaccination suggest a possible link to the injection procedure and highlight the need to adhere to recommendations regarding skin preparation and the selection of the appropriate needle length and injection site.